Characteristics of Vitamin D concentration in elite Israeli Olympic athletes - Abulafia, O.; Ashkenazi, E.; Epstein, Y.; Eliakim, A.; Nemet, D. (Nutrients, 2024)
Background: The prevalence of vitamin D deficiency has been a growing concern in recent years. Vitamin D is important in many of the body`s physiological systems, such as the musculoskeletal, cardiovascular and immune functions. A deficiency of vitamin D in athletes may negatively impact both muscle functions and recovery and, thus, affect performance and increase the risk of injury. Many studies assessed the prevalence of vitamin D deficiency in athletes; however, as of today, there are no official recommendations/protocols for screening vitamin D levels in athletes, and only a few studies were performed in male and female elite athletes (i.e., Olympic level), in different sport disciplines.